The effect of book Piracy on the Nigerian publishing industry: publishers’ perspective (2022)
It is a known fact that book piracy has affected the Nigerian book Publishing industry negatively. The opinion of book publishers on the menace of book piracy in the Nigerian Publishing industry needs investigation, which is the interest of this study. Descriptive research design was adopted for the study of svc Publishing houses in Ibadan, Oyo State, Nigeria. Questionnaire was used as instrument for data collection. The purposive sampling technique was employed to select 80 staff from the Publishing houses under investigation. Collected data were analysed using simple percentages. The findings revealed that the cost of Publishing in Nigeria is high, which made the prices of books unaffordable to the buyers, thereby creating a vacuum for piracy to thrive. The menace of book piracy has adversely affected the financial gains of both authors and publishers. Book piracy has also caused moral harms to both authors and publishers thereby discouraging upcoming writers from developing new manuscripts. It was therefore recommended that piracy should be fought through collaborative efforts of all the actors in the book industry and the government at all levels. Furthermore, the government should ensure that the aspect of the laws on intellectual property protection is enforced. Also, the public should be sensitised through the media and other awareness campaigns on the harmful effects of piracy as well as against patronising pirates